Answer:
Let the quadratic equation be [tex]2x^2 +12x+ 6[/tex]
Step 1: Take the coefficients of the [tex]x^2[/tex] term and divide the entire equation
Here the coefficient of [tex]x^2[/tex] is 2
So dividing the entire equation by 2, we get
[tex]x^2 +6x+ 3[/tex]
Step 2: Move the constant term to the right side of the equation
[tex]x^2 +6x = - 3[/tex]
Step 3: Complete the square on the left side of the equation and balance this by adding the same number to the right side of the equation
[tex](\frac{b}{2})^2[/tex] = [tex](\frac{6}{2})^2[/tex] = [tex](3)^2[/tex] = 9
[tex]x^2 +6x + 9 = - 3 +9[/tex]
[tex](x+3)^2 = 6[/tex]
Step 4: Take the square root on both sides of the equation
[tex](x+3) = \sqrt{6}[/tex]
[tex]x+3 = \pm 2.45[/tex]
Step 5 Subtract 3 from both sides:
[tex]x+3 - 3 = \pm 2.45 -3[/tex]
[tex]x = \pm 2.45 -3[/tex]
x = 2.45 - 3 or x = -2.45 - 3
x = - 0.55 or x = -5.45